2020
DOI: 10.1111/jonm.13224
|View full text |Cite
|
Sign up to set email alerts
|

Testing the structural equation model of the influence of nurses’ spiritual well‐being and caring behaviour on their provision of spiritual care to patients

Abstract: Aim To test a proposed model that determined the effects of nurses’ spiritual well‐being and caring behaviour on their provision of spiritual care to patients. Background The spiritual dimension of caring gained attention in the recent past as it is recognized to bring positive patient outcomes. Methods A cross‐sectional, descriptive, correlational design was used in the study. Data were collected from 300 registered nurses working in the hospitals in Pampanga, Philippines. Partial least square structural equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Thus to conclude, because this review is the first that considers the interplay between spirituality, religiosity, and well‐being, we argue that the juxtaposition of Ryff's (1989) theory with insights from spirituality and religion holds much promise. Our study thereby constitutes specific contributions to Ryff's (1989) theory through offering novel theorizations of well‐being (i.e., spiritual well‐being, see Biag & Angeles Jr, 2021).…”
Section: Discussionmentioning
confidence: 96%
“…Thus to conclude, because this review is the first that considers the interplay between spirituality, religiosity, and well‐being, we argue that the juxtaposition of Ryff's (1989) theory with insights from spirituality and religion holds much promise. Our study thereby constitutes specific contributions to Ryff's (1989) theory through offering novel theorizations of well‐being (i.e., spiritual well‐being, see Biag & Angeles Jr, 2021).…”
Section: Discussionmentioning
confidence: 96%
“…The authors concluded that their findings affirm previous research that suggests nurses provide SC infrequently. On the same line, Biag and Angeles found that psychosocial care was often or always given, whereas spiritual care was offered only occasionally [36]. Even among highly religious nurses, spiritual care therapeutics are rarely offered to patients [35].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, extroverts tend to view work positively and are more courageous and responsible when solving various problems in the workplace. They are also more likely to feel more happiness, and this significantly predicts the provision of humanistic care to patients [ 39 ]. People with high psychoticism scores may lack sympathy, carelessness, or unkindness to others at work, and cannot integrate well into society or interpersonal relationships.…”
Section: Discussionmentioning
confidence: 99%